MENGOPTIMALKAN PERSEDIAAN BAHAN BAKU UTAMA BEGACRON BLACK GI 200%: STUDI KASUS PT COLORINDO ANEKA CHEMICALS - Sutono, Sutono; Taufik, Taufik (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Main problem in planning and controlling supply is to determine how many order of the main material or raw material is done and when the order should be done so the production can smoothly run and increase the efficientcy of the production process. The wrong supply control will make customerâs demand cannot be fulfilled on time. Besides that, the trust and customer opinion on company will decline. Therefore, a planning and control supply is needed to achieve a maximum result.